Institutions of the Past: The Potential of Organizational Theory in Collective Memory Studies - Anna Kolotovkina (Journal of Economic Sociology, 2024)
The article is devoted to the potential of organizational theory in memory studies. The existing approaches to the study of themes at the intersection of historical memory and organizations are noted. Firstly, this is the institutional approach in memory studies, which is characterized by a thorough description of individual cases but a lack of comparison, as well as a narrow understanding of what can be considered an institution of memory. Secondly, there are organizational memory studies (OMS), which are aimed primarily at studying the formation and reproduction of the history of specific organizations and which lack attention to the theoretical findings of memory studies. The main weakness of the described methodological solutions is their weak theoretical and disciplinary permeability, which leads to parallel research work in areas that are little interested in each other. An alternative methodological move may be the application of the sociology of organizations to studies of museums, archives, educational institutions, and other mnemonic actors. The article examines three key areas of organizational sociology: new institutionalism (focusing on isomorphism, decoupling, and organizational discretion), resource dependence theory, and organizational ecology. The approaches described are illustrated by examples from empirical studies on collective memory, as well as cases relevant to social and historical research. It is noted that organizational theory can be used to analyze commemorative practices, (re)production of identity, and relations with the state. It helps explain variations in practices across institutions, links established organizational traditions with their actions in the present, and typologizes organizations on new grounds.